Contribution of Chicken Feather Fiber to the Dielectric Properties of Unsaturated Polyester Matrix Composites - Kiew, K. S.; S., Hamdan; Md. R., Rahman (ENCON 2013, 2013)
The dielectric properties of chicken feather fiber unsaturated polyester composites have been studied with reference to the fiber loading and frequency. The composites fabricated were exposed for dielectric studies in the wide range of frequency from 60 Hz to 1 MHz. Experiments were conducted to examine the suitability of this composite as a dielectric material. The chicken feather fiber composites exhibit an overall comparable low dielectric constant, dissipation factor and loss factor, as compared to conventional commercial Printed Circuit Board (PCB) material. The dielectric values were high for the composites with fiber contents at 40%. The dielectric value increments were high at low frequencies, which gradually reached significantly lower values at higher frequencies. The research outcome indicates that the chicken feather fiber composites would be suitable for application as high speed Printed Circuit Board (PCB) material with good frequency stability at 1 MHz. Lastly, an attempt was made to correlate the experimental values with theoretical calculations.